Assessment of Quality in Health Care Delivery - On an Example of a Baseline Survey on Clients’ Satisfaction and Staffs’ self assessed Capacity and Working Conditions in two remote Provinces of Northern Vietnam - Gaby Zeck (2009)
Within the framework of the GTZ project Contribution to the improvement of health services in Cao Bang and Son La provinces a survey to assess the quality of health care delivery was conducted. This survey particularly intended to find out which aspects contribute to clients’ satisfaction respectively dissatisfaction with received health services in the cultural and geographical context of the remote and mountainous provinces Cao Bang and Son La. Understanding patients’ perception of quality of health care services is important in order to be able to improve the quality of services according to the clients needs, and hence to develop measures to increase the low utilization rate of health facilities in rural and remote areas of Vietnam. The survey furthermore aimed to assess health staffs capacity in both project provinces and to identify areas in which staff is in need for additional training and support to ensure services appropriate to clients needs.